Willingness and influential factors of parents of 3-6-year-old children to vaccinate their children with the COVID-19 vaccine in China. Issue 11 (2nd November 2021) - Wan, Xiao; Huang, Haitao; Shang, Jia; Xie, Zhenxing; Jia, Ruiying; Lu, Guangli; Chen, Chaoran
ABSTRACT: The impact of Coronavirus disease 2019 (COVID-19) on children aged 3–6 can be severe. Vaccination for COVID-19 is one of the most important primary preventative measures to reduce disease transmission. Parents are hesitant to vaccinate their children against COVID-19 because it was reported in the news that some adults have had adverse reactions to the vaccine. This study aims to investigate the willingness of Chinese parents of 3–6 year old children to vaccinate them with the COVID-19 vaccine and identify what factors influence their decisions. A survey was conducted using a two-stage stratified random sampling method from December 2020 to February 2021. We used univariate analysis and multivariate binary logistic analysis to explore potential factors that may determine the acceptance of the COVID-19 vaccine. Of the 468 parents who participated, 86.75% were willing to vaccinate their children with the COVID-19 vaccine. Parents who were female (OR = 2.591; 95% CI: 0.432–4.689), recognized their children in the high-risk category (OR = 2.494; 95% CI:1.244–5.002), often followed-up with COVID-19 vaccine-related information (OR = 9.065; 95% CI: 3.220–28.654), believed in the safety of the COVID-19 vaccine (OR = 3.068; 95% CI: 1.313–7.168), or thought the COVID-19 vaccine could prevent COVID-19 (OR = 13.750; 95% CI: 2.516–75.140) were more willing to vaccinate their children. To ease parents' hesitation about vaccines, the authority organization should release updated information on the safety and reliability of vaccines, target gender-specific health education for parents, and ask the media to report scientifically support information.